Biofilm formation by Salmonella sp. in the poultry industry: Detection, control and eradication strategies - Merino, Lina Ethel; Procura, Francisco; Trejo, Fernando Miguel; Bueno, Dante Javier; Golowczyc, Marina Alejandra (Elsevier, 2019)
Salmonella represents an important global public health problem and it is an emerging zoonotic bacterial threat in the poultry industry. Diverse registered human cases of salmonellosis shown poultry origins. Various control measures have been employed both at the farming and processing levels to address it. This review focuses on traditional and new detection techniques of biofilm formation by Salmonella spp. and different approaches that can be used to prevent and/or control biofilm formation by these bacteria. A number of methodologies based on different approximations have been recently employed to detect and evaluate bacteria attached to surfaces, including real-time polymerase chain reaction (PCR), confocal laser scanning microscopy and Optical Coherence Tomography. Due to persistence of Salmonella biofilm in food processing environments after cleaning and sanitation, control and eradication strategies in poultry industry should be constantly studied. In this sense, the use of several alternatives to control Salmonella biofilm formation, such as lactic acid bacteria, phagetherapy, extracts from aromatic plants, quorum sensing inhibitors, bacteriocins and nanomaterials, have been successfully tested and will be reviewed.